PELATIHAN PENGELOLAAN OBAT AMAN DAN KAMPANYE KESADARAN EFEK SAMPING DI LINGKUNGAN MASYARAKAT - Istiqomah, Istiqomah; Punjastuti, Budi; Yunitasari, Pritta; Annarahayu, Luthfi (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2024)
Appropriate and safe medication use is essential for maintaining public health across all age groups. Improper home medication management, including incorrect storage, irregular dosing schedules, and limited awareness of side effects, may increase health risks. This community service program aimed to improve knowledge, skills, and awareness regarding home medication management and side effect awareness. The activity was conducted in Dusun Destan, Bambanglipuro, Bantul Regency, involving 66 participants from various age groups. An educational approach was applied through interactive counseling sessions supported by educational leaflets containing information on proper medication storage, dosing schedule management, and early recognition and management of medication side effects. Evaluation was carried out informally through observation and question-and-answer sessions. The results demonstrated a noticeable improvement in participants’ knowledge in all discussed aspects, including medication storage, dosing schedules, and awareness of side effects. Participants also showed increased concern for medication safety in daily use. This activity has the potential to reduce medication-related errors and contribute to improved quality of life through safer and more rational medication use at the household level.